2015
DOI: 10.1108/ijoa-04-2012-0584
|View full text |Cite
|
Sign up to set email alerts
|

Transitivity, hierarchy and reciprocity of organizational communication network during crisis

Abstract: Purpose – This paper aims to explore changes in communication networks during organizational crisis. In the literature, various terms such as organizational mortality, organizational death, bankruptcy, decline, retrenchment and failure have been used to characterize different forms and facets of organizational crisis. Communication network studies have typically focussed on nodes (e.g. individuals or organizations), relationships between those nodes and subsequent affects of these relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…It is particularly useful to manage global pandemics (Kilroy et al, 2023;Garner, 2017;Schneider & Spieth, 2013) from a perspective of SET (Granovetter,1973;Blau,1964;Kong et al, 2019;Murshed et al, 2015). The buyer-seller relationship can, however, become stronger after a crisis meaning that, the relevance of various marketing strategies to cope up the digital agility capacity in family business firms during turbulent times become immensely essential (Tsai et al, 2010;Kong et al, 2019).…”
Section: Social Exchange Theory (Set)mentioning
confidence: 99%
“…It is particularly useful to manage global pandemics (Kilroy et al, 2023;Garner, 2017;Schneider & Spieth, 2013) from a perspective of SET (Granovetter,1973;Blau,1964;Kong et al, 2019;Murshed et al, 2015). The buyer-seller relationship can, however, become stronger after a crisis meaning that, the relevance of various marketing strategies to cope up the digital agility capacity in family business firms during turbulent times become immensely essential (Tsai et al, 2010;Kong et al, 2019).…”
Section: Social Exchange Theory (Set)mentioning
confidence: 99%
“…Zinko et al (2012b) showed integrity to be an essential component of leader reputation. Likewise, Murshed et al (2015) call attention to the relationship between perceived integrity and personal reputation. When discussing the concept of a social reputation (i.e.…”
Section: Integrity Reputationmentioning
confidence: 99%
“…In recent years, many scholars have paid attention to inter-organization communication between organization (Basch et al, 2018;Du et al, 2012;Friedkin, 1982;Liu et al, 2015;Murshed et al, 2015). Researchers have reported that interorganizational communication affects many aspects of supply chain outcomes.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%